Pile of Blocks to Improve Understanding of Metaphorical Language for Elementary School Students - Sumandari, Ni Wayan Gita; Maria Goreti Rini Kristiantari; I Gede Margunayasa (Mimbar Ilmu, 2025)
Students' difficulties in understanding and applying metaphorical expressions in Indonesian language learning have led to low engagement and poor writing performance. This issue is exacerbated by the lack of interactive learning media that are appropriate for the developmental characteristics of elementary students in facilitating their comprehension of figurative language. This study aims to develop the Pile of Blocks learning media to support the understanding of metaphorical expressions in the Indonesian language. This research employs a research and development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects include experts—namely a content expert, an instructional design expert, and a media expert—as well as Grade V elementary school students. Data were collected through interviews, questionnaires, and cognitive learning outcome tests. The instruments used consisted of non-test instruments (interview guidelines and questionnaires) and test instruments (pre-test and post-test). The data analysis techniques included qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis using a paired sample t-test to measure the effectiveness of the developed media. The final results indicate that the Pile of Blocks media is effective in improving students’ understanding of metaphorical material, as evidenced by the increase in average scores from 59 (pre-test) to 76.1 (post-test), with a paired sample t-test result of 7.23 > 2.021 at the 5% significance level. It can therefore be concluded that the Pile of Blocks media is both feasible and effective for enhancing students’ understanding of figurative language in Grade V Indonesian language learning at the elementary school level.